Legal regulation of the medicines reimbursement in Ukraine: implementation of international experience - Maika, Nataliia; Trufanova, Yulia; Lukashov, Rostyslav (Актуальні проблеми правознавства, 2023)
The article is devoted to the problems of legal adjusting of relations concerning the reimbursement of the cost of medical services by the state for the benefit of subjects of the pharmaceutical industry: manufacturers, pharmacies, healthcare institutions, etc. The nature of reimbursement relations was investigated. Current domestic legislation on reimbursement is fairly new and is the result of implementing the principles of regulatory policy in the field of health care adopted in the EU. It was also developed to implement the provisions of the Association Agreement between Ukraine and the EU. Therefore, it is logical to conclude that the domestic legislation has a number of disadvantages, in particular regarding the extremely narrow list of diseases for the treatment of which medicines can be reimbursed. In addition, the fact that only the NHSU may be party to reimbursement agreements significantly reduces the opportunities for practical implementation of state guarantees in the sphere of public health care. Instead, expanding the scope of subjective relationships at the expense of local governments will significantly increase the effectiveness of public policies on the availability of medicines. The analysis of foreign experience has made it possible to establish the effectiveness of such principles of the reimbursement system as therapeutic expediency and value for money / treatment. These principles are the foundations of the reimbursement systems in Germany, France, the United Kingdom, the Baltic States, the Czech Republic, Slovakia, etc. The attention is also drawn to the experience of the United Kingdom in maintaining a register of medicinal products which may be subject to reimbursement mechanisms, the inclusion to which is based solely on information about the efficacy of such medicinal products as confirmed by clinical trials. All of this requires further study in order to introduce the legal support of the medicines reimbursement relations into the domestic practice.